Analisis Upaya Petani dalam Meningkatkan Hasil Produksi Padi Menurut Perspektif Bisnis Syariah (Studi Kasus Kelompok Tani Jorong Kubu Gadang Kec.Payakumbuh Kab. Lima Puluh Kota) - Yunia Hamni; Novera Martilova (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
Efforts to increase rice production are very important because they can increase farmers' income in the farming business. The purpose of this research is to find out how farmers are making efforts to increase rice production in the Jorong Kubu Gadang farmer group, Payakumbuh Kab. Limapuluh Kota and what obstacles there are. experienced in an effort to increase rice production in the Jorong Kubu Gadang farmer group. This research is descriptive research with a qualitative approach. Data collection techniques used are observation, interviews and documentation. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. And the number of informants in this research is 1 person. The results of this research shows that the efforts made by the Jorong farmer group, Payakumbuh district, Fifty cities, are in the form of counseling, training and outreach, including agricultural counseling, training in the use of technology in the Jorong Kubu farmer group. gadang, agribusiness and horticulture training, socialization on fertilizer and pesticide selection, training on selecting superior seeds and making irrigation channels.